Tolerating Factor VIII: Recent Progress - Lacroix-Desmazes, Sebastien; Voorberg, Jan; Lillicrap, David; Scott, David W.; Pratt, Kathleen P. (Frontiers in Immunology, 2020)
Development of neutralizing antibodies against biotherapeutic agents administered to prevent or treat various clinical conditions is a longstanding and growing problem faced by patients, medical providers and pharmaceutical companies. The hemophilia A community has deep experience with attempting to manage such deleterious immune responses, as the lifesaving protein drug factor VIII (FVIII) has been in use for decades. Hemophilia A is a bleeding disorder caused by genetic mutations that result in absent or dysfunctional FVIII. Prophylactic treatment consists of regular intravenous FVIII infusions. Unfortunately, 1/4 to 1/3 of patients develop neutralizing anti-FVIII antibodies, referred to clinically as “inhibitors”, which result in a serious bleeding diathesis. Until recently, the only therapeutic option for these patients was “Immune Tolerance Induction”, consisting of intensive FVIII administration, which is extraordinarily expensive and fails in ~30% of cases. There has been tremendous recent progress in developing novel potential clinical alternatives for the treatment of hemophilia A, ranging from encouraging results of gene therapy trials, to use of other hemostatic agents (either promoting coagulation or slowing down anti-coagulant or fibrinolytic pathways) to “bypass” the need for FVIII or supplement FVIII replacement therapy. Although these approaches are promising, there is widespread agreement that preventing or reversing inhibitors remains a high priority. Risk profiles of novel therapies are still unknown or incomplete, and FVIII will likely continue to be considered the optimal hemostatic agent to support surgery and manage trauma, or to combine with other therapies. We describe here recent exciting studies, most still pre-clinical, that address FVIII immunogenicity and suggest novel interventions to prevent or reverse inhibitor development. Studies of FVIII uptake, processing and presentation on antigen-presenting cells, epitope mapping, and the roles of complement, heme, von Willebrand factor, glycans, and the microbiome in FVIII immunogenicity are elucidating mechanisms of primary and secondary immune responses and suggesting additional novel targets. Promising tolerogenic therapies include development of FVIII-Fc fusion proteins, nanoparticle-based therapies, oral tolerance, and engineering of regulatory or cytotoxic T cells to render them FVIII-specific. Importantly, these studies are highly applicable to other scenarios where establishing immune tolerance to a defined antigen is a clinical priority.